The Elite / 2. - Cass, Kiera (Cass, Kiera. Selection novel, 2013)
"Sixteen-year-old America Singer is one of only six girls still competing in the Selection--but before she can fight to win Prince Maxon and the Illean crown, she must decide where her own heart truly lies"--